Nitric oxide-generating compound and bio-clickable peptide mimic for synergistically tailoring surface anti-thrombogenic and anti-microbial dual-functions - Han Yu; Shaoxing Yu; Hua Qiu; Peng Gao; Yingzhong Chen; Xin Zhao; Qiufen Tu; Minggang Zhou; Lin Cai; Nan Huang; Kaiqin Xiong; Zhilu Yang (Bioactive Materials, 2021)
Application of extracorporeal circuits and indwelling medical devices has saved many lives. However, it is accompanied with two major complications: thrombosis and infection. To address this issue, we apply therapeutic nitric oxide gas (NO) and antibacterial peptide for synergistically tailoring such devices for surface anti-thrombogenic and antifouling dual functions. Such functional surface is realized by stepwise conjugation of NO-generating compound of 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid (DOTA) chelated copper ions (Cu-DOTA) and dibenzylcyclooctyne- (DBCO-) modified antimicrobial peptide based on carbodiimide and click chemistry respectively. The integration of peptide and Cu-DOTA grants the modified surface the ability to not only efficiently inhibit bacterial growth, but also catalytically generate NO from endogenous s-nitrosothiols (RSNO) to reduce adhesion and activation of platelets, preventing the formation of thrombus. We envision that the stepwise synergistic modification strategy by using anticoagulant NO and antibacterial peptide would facilitate the surface multifunctional engineering of extracorporeal circuits and indwelling medical devices, with reduced clinical complications associated with thrombosis and infection.